Studies on host range of Alternaria spp. causing blight disease in linseed: STUDIES ON HOST RANGE OF ALTERNARIA SPP. CAUSING BLIGHT DISEASE IN LINSEED - H H ASMA; K AJITHKUMAR; A S SAVITHA; S T YENJERAPPA; M R GOVINDAPPA; D KRISHNAMURTHY (Journal of Oilseeds Research, 2021)
Alternaria blight is one of the most serious diseases of linseed caused by different Alternaria spp. The genus Alternaria Nees ex Fr. is widely distributed all over the world and is represented by a number of species. The genus occupies a prime position and is significantly important as its members are well known in causing wide spread diseases of economic plants such as cereals, oilseed crops, spices, vegetables and ornamentals. The studies on host range of Alternaria spp. revealed that the pathogen was unable to infect any of the crop plants taken for study under the pot conditions but showed mycelial growth on all the crops tested through detached leaf technique under laboratory condition. The maximum mycelial growth of Alternaria spp. was noticed on carrot grass (9.56 mm) followed by groundnut (8.82 mm), whereas, minimum mycelial growth was observed on sesame (2.52 mm). Therefore, based on this host range test, it can be concluded that Alternaria spp., infecting linseed may also be pathogenic to other hosts only under controlled and favourable conditions.